2000
DOI: 10.1093/nar/28.20.3846
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of the fourth subunit (Dpb4p) of DNA polymerase varepsilon in Saccharomyces cerevisiae

Abstract: DNA polymerase epsilon (Polepsilon) of Saccharomyces cerevisiae is purified as a complex of four polypeptides with molecular masses of >250, 80, 34 (and 31) and 29 kDa as determined by SDS-PAGE. The genes POL2, DPB2 and DPB3, encoding the catalytic Pol2p, the second (Dpb2p) and the third largest subunits (Dpb3p) of the complex, respectively, were previously cloned and characterised. This paper reports the partial amino acid sequence of the fourth subunit (Dpb4p) of Polepsilon. This protein sequence matches par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 35 publications
1
74
0
2
Order By: Relevance
“…Therefore, p17 might mediate an interaction or a switching between pol ⑀ and huCHRAC to facilitate efficient replication of the highly ordered heterochromatin. Deletion mutants of DPB4, the S. cerevisiae homolog of human pol ⑀ p17, are viable but have a prolonged S-phase (15), supporting the proposal that pol ⑀ might be necessary for the efficient replication of heterochromatic DNA though another polymerase (presumably pol ␦), and other chromatin-remodeling mechanisms can operate in its place.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Therefore, p17 might mediate an interaction or a switching between pol ⑀ and huCHRAC to facilitate efficient replication of the highly ordered heterochromatin. Deletion mutants of DPB4, the S. cerevisiae homolog of human pol ⑀ p17, are viable but have a prolonged S-phase (15), supporting the proposal that pol ⑀ might be necessary for the efficient replication of heterochromatic DNA though another polymerase (presumably pol ␦), and other chromatin-remodeling mechanisms can operate in its place.…”
Section: Discussionmentioning
confidence: 62%
“…Human pol ⑀ has four subunits, a large catalytic subunit, p261, and three associated subunits, p59, p12, and p17 (11,12). Likewise, Saccharomyces cerevisiae pol ⑀ has a catalytic subunit of 256 kDa, POL2, and has three associated subunits encoded by DPB2, DPB3, DPB4 (8,(13)(14)(15).…”
mentioning
confidence: 99%
“…DPB3 and DPB4 encode the two nonessential components of DNA polymerase e (Pol e) and have been implicated in replication fork progression (Araki et al 1991;Dua et al 1998;Ohya et al 2000). In addition, previous studies have demonstrated roles for Dpb3 and Dpb4 in telomeric silencing (Tsubota et al 2006) and have shown that Dpb4 is also a component of the Isw2 complex (Iida and Araki 2004;McConnell et al 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Only Dpb2 is essential for viability and normal S phase progression (Araki et al, 1991a). Although both Dpb3 and Dpb4 are not required for cell viability, deletion of the genes encoding these proteins does result in partial defects in DNA replication (Araki et al, 1991b;Ohya et al, 2000). Interestingly, both Dpb3 and Dpb4 contain histone-fold motifs, suggesting these proteins might be involved in chromatin remodeling (Araki et al, 1991b;Li et al, 2000;Ohya et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although both Dpb3 and Dpb4 are not required for cell viability, deletion of the genes encoding these proteins does result in partial defects in DNA replication (Araki et al, 1991b;Ohya et al, 2000). Interestingly, both Dpb3 and Dpb4 contain histone-fold motifs, suggesting these proteins might be involved in chromatin remodeling (Araki et al, 1991b;Li et al, 2000;Ohya et al, 2000). Based on the existence of these motifs, it has been proposed these subunits might facilitate replication through heterochromatic regions of DNA (Fuss and Linn, 2002).…”
Section: Introductionmentioning
confidence: 99%